Difficulties toward third level students in the department of Arabic language for both Education for Women College and Ibn Rushd/University of Baghdad for the studying of Arabic language curriculum: Difficulties toward third level students in the department of Arabic language for both Education for Women College and Ibn Rushd/University of Baghdad for the studying of Arabic language curriculum (Journal of the College of Education for Women, 2019)
AbstractThe curriculum is amodern science which reflects the social philosophy andwhat it needs . It searches for amothod that limits the knowledge that theindiridual gets in the society and the sorts of the culture that suits the enrironmentin which they live. It also clears for them their history and their great in heritance.It has a great in flunce in their mental growth ,and it teacher the students newroles in the thin king ,and training then on what they have learned . According tothere points the problem concentrats on the mostimpotant difficulties which facerthestudents in studing Arabic langnage text-booksIn spite of the great care that the text taker but it is full of subjects and studieswhich are far from the learnersneed .The recent research aims to an knowledge the most important difficulties thatface the .students of the college of education for girls and the college of Ibn –Rushad,Baghdad university in teaching Arabic language text-books . This studyincludes ( ) students both girls and boys this research is prepared and itcontained ( ) points.In itsstatistic treatment for the statements many methods were used such asweighted mean the percentage . And the research shows that the most of theitems which were high in rate “The weakness of the teachers in their ability toexplain the relation ship between the Arabic language and the texts-books “. Thedeclined copacity- that exists in the university to apply methods “and”they dependan the written tests to appreciate the students marks”.